CTNI-36. SAFETY OF ONC201 ADMINISTERED TWO CONSECUTIVE DAYS PER WEEK IN PEDIATRIC H3 K27M-MUTANT GLIOMA PATIENTS. (12th November 2021) - Gardner, Sharon; Koschmann, Carl; Tarapore, Rohinton; Allen, Jeffrey; Zaky, Wafik; Odia, Yazmin; Hall, Matthew; Daghistani, Doured; Khatib, Ziad; Aguilera, Dolly; MacDonald, Tobey; de Blank, Peter; et al.
Abstract: ONC201, an anti-cancer DRD2 antagonist and ClpP agonist, is in Phase II trials for adult H3 K27M-mutant diffuse midline gliomas. The recommended phase 2 dose (RP2D) of 625mg ONC201 once a week has been established as a biologically active dose that is well tolerated in adult and pediatric populations. Radiographic regressions with single agent ONC201 have been reported in recurrent H3 K27M-mutant glioma patients. In another study, twice/week dosing was explored in adult patients and deemed to be safe (no DLTs observed). This warranted exploration of twice/week dosing in pediatric patients and will be discussed in this presentation. This multi-arm, dose-escalation and dose-expansion trial (ONC014; NCT03416530) determined the pediatric RP2D of ONC201 administered once per week and twice per week on two consecutive days. ONC201 was orally administered and scaled by body weight. Dose escalation was performed by a 3 + 3 design beginning with two 125mg capsules less than the adult RP2D equivalent. Twelve children (8 females; 4 males) with H3 K27M-mutant gliomas (pons: 8; thalamus: 2; spinal cord: 2) aged 4-19 years have been treated post-radiation: 3 at dose level -1; 3 at dose level 1; 6 as part of the dose expansion cohort on dose level 2. Median KPS was 90 (range 70-100). One treatment cycle was 21 days (6 doses), which also defined the DLT window. Patients were on-treatment for a median length of 4 cycles (range: 2-11). Twice weekly dosing of ONC201 was tolerated well, as observed with weekly dosing, with no instance of DLT. A total of 4 SAEs were reported, none of which were related to the study drug. The most common AEs (regardless of relatedness) included headache, facial nerve disorder, abducens nerve disorder, nausea, fatigue and ataxia. Additional safety data, PK, and clinical outcomes from this arm will be reported.